2019
DOI: 10.1016/j.ejvs.2019.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Metabolism Disturbances and Arteriovenous Fistula Maturation

Abstract: WHAT THIS PAPER ADDS Patients with chronic kidney disease have disturbances of mineral metabolism, which may interfere with the vascular remodelling process required for successful maturation of arteriovenous fistulae. To the authors' knowledge, this is the first study of end stage renal disease patients, either undergoing or anticipated to soon require maintenance haemodialysis, to assess relationships between serum mineral metabolites and abnormalities of vein segments used to create haemodialysis arterioven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Without Doppler ultrasound, stenosis leading to AVF failures may be misdiagnosed as thrombosis. Secondly, the impact of mineral metabolism disturbances on AVF maturation remains controversial [ 44 , 45 ]. Despite this, the potential association between the measurable markers of mineral metabolism and functional AVF maturation was not examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Without Doppler ultrasound, stenosis leading to AVF failures may be misdiagnosed as thrombosis. Secondly, the impact of mineral metabolism disturbances on AVF maturation remains controversial [ 44 , 45 ]. Despite this, the potential association between the measurable markers of mineral metabolism and functional AVF maturation was not examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…25(OH)D fundamentally helps maintain human skeleton [ 19 ]. As suggested by existing studies, the repair process of ONFH is similar to the mechanism of microfracture repair, which is a high rate of the bone turnover process [ 22 ]. As reported from this study, the non-collapsed group t-P1NP and β-CTx were significantly higher than the collapsed group.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the non-collapsed group CSI, BSI and ISI were significantly larger than the collapsed group. CSI, constructed from structural engineering principles, measures the maximum compressing load that the femoral neck could withstand per unit thickness cross-sectional slice and the unit of normal compression load exerted on the femoral neck [ 22 ]. As indicated by the calculation formulas of CSI, BSI and ISI, when BMD, weight and height are identical, the larger the FNW, the larger CSI, BSI and ISI will be [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other vascular calcification markers such as fetuin-A, osteopontin, and bone morphogenetic protein-7 were also associated with the development of AVF complications in a cohort of dialysis patients ( 96 ). However, a prospective clinical study came to the opposite conclusion ( 97 ). The study concluded that serum concentrations of mineral metabolites in patients were not substantially related to AVF failure.…”
Section: Molecular Mechanism Of Arteriovenous Fistula Failurementioning
confidence: 99%